Financial Sector Assessment Program : Brazil - IOSCO Objectives and Principles of Securities Regulation - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
The Comissao de Valores Mobiliarios - Brazil Securities Commission (CVM) has made substantial progress since the 2002 Financial Sector Assessment Program (FSAP). In 2002 the International Organization of Securities Commissions (IOSCO) assessment rated 8 principles fully implemented and 22 principles partly implemented. The 2012 assessment rates 26 principles fully implemented, 5 broadly implemented, and 6 partly implemented. Principle 38 is not rated, as a separate Report on Observance and Codes (ROSC) on systemically important payment systems was conducted as part of this FSAP update. The detailed assessment highlights significant improvements in the risk-based inspection program, adoption of an innovative issuer disclosure system, a stronger enforcement program and the adoption of International Financial Reporting Standards (IFRS). Long-standing issues on corporate governance and the protection of minority shareholders continue to be challenges. Finally, recommendations to improve prudential regulation of Collective Investment Schemes (CIS) are discussed.